2019
DOI: 10.1084/jem.20181868
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ signaling in germinal center B cells promotes the transition from light zone to dark zone

Abstract: B cells in germinal centers (GCs) cycle between light zone (LZ) and dark zone (DZ). The cues in the GC microenvironment that regulate the transition from LZ to DZ have not been well characterized. In Peyer’s patches (PPs), transforming growth factor-β (TGFβ) promotes IgA induction in activated B cells that can then differentiate into GC B cells. We show here that TGFβ signaling occurs in B cells in GCs and is distinct from signaling that occurs in activated B cells in PPs. Whereas in activated B cells TGFβ sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…FOXO1 regulates the expression of numerous genes, including Cxcr4 , which encode a G-protein-coupled receptor necessary for migration of B cells to the dark zone 82 , 84 . Transforming growth factor-β (TGFβ) and IL-10 signalling in GC B cells promote FOXO1 expression 85 , 86 . The transcriptional programme regulated by FOXO1 largely overlaps with that of BCL-6, suggesting that FOXO1 and BCL-6 cooperate to support the dark zone state 82 .…”
Section: Regulation Of Gc B Cell Maintenancementioning
confidence: 99%
“…FOXO1 regulates the expression of numerous genes, including Cxcr4 , which encode a G-protein-coupled receptor necessary for migration of B cells to the dark zone 82 , 84 . Transforming growth factor-β (TGFβ) and IL-10 signalling in GC B cells promote FOXO1 expression 85 , 86 . The transcriptional programme regulated by FOXO1 largely overlaps with that of BCL-6, suggesting that FOXO1 and BCL-6 cooperate to support the dark zone state 82 .…”
Section: Regulation Of Gc B Cell Maintenancementioning
confidence: 99%
“…In addition, we detected lower levels of FOXO1 protein known to accompany its phosphorylation upon gating either total GC B cells or LZ B cells (Supplemental Figure 6, C and D, and ref. 44). Thus, ROCK2 promotes FOXO1 activation and controls a FOXO1-repressed gene set in GC B cells, probably through its ability to regulate AKT activity.…”
Section: Rock2 Induces Expression Of the Cholesterol Biosynthesis Patmentioning
confidence: 99%
“…Transforming growth factor (TGF)-β signaling is involved in several processes regulating B cell maturation. For instance, a study showed that IgD+ B cells were observed in the presence of TGF-β signaling, whereas genetic deletion of the receptor led to complete loss of IgD ( Albright et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%